1993
DOI: 10.1159/000263759
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Uterine Doppler Waveform during Pregnancies Complicated by Diabetes

Abstract: Diabetes, whether or not it is insulin deficient, is frequently associated with vascular complications during pregnancy. It is accepted nowadays that the uterine artery velocity waveform is predictive concerning pregnancy-induced hypertension (PIH) and its complications. It thus seemed interesting to analyse the predictivity of vascular complications of diabetes by using uterine artery velocity waveforms. We have thus explored 37 diabetic patients [group 1: insulin-deficient diabetes (IDD), n = 10; group 2: ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…After independent review of the English manuscripts under masked conditions, 30 articles 6,16–44 were considered to be eligible to be included in the overview. The agreement concerning eligibility was 92% (kappa 0.85).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After independent review of the English manuscripts under masked conditions, 30 articles 6,16–44 were considered to be eligible to be included in the overview. The agreement concerning eligibility was 92% (kappa 0.85).…”
Section: Resultsmentioning
confidence: 99%
“…Two of these 6,18 were excluded from the overview when the first authors of these articles confirmed that the data had been reported elsewhere. Thus, 28 articles 16–17,19–44 were included into the overview; pre‐eclampsia was reported in 22 studies (79%) 16–17,19–20,22–25,27,28–33,38,40–42,44 , intrauterine growth retardation was reported in 24 studies (86%) 16–17,21–23,25,27–44 and eight studies (28%) 17,23,25–26,28,31,36–37 reported on perinatal death (Table 1). Of the eight articles that reported on perinatal death, the gestational age for fetal viability was defined as 24 weeks of gestation in one study 36 , 18–22 weeks of gestation in another study 17 and undefined in the remaining studies 23,25–26,28,31,37 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on UtA Doppler examination in pregnancies complicated by GDM were mainly conducted in the second half of the pregnancy, when GDM was diagnosed. These studies suggested that UtA velocimetry was more likely to be abnormal in women with GDM who also developed placental‐related complications, such as PE and/or fetal growth restriction, compared with those who did not.…”
Section: Discussionmentioning
confidence: 99%
“…Gestational diabetes mellitus (GDM) is known to be associated with increased prevalence of PE. Doppler studies performed in the late second or third trimesters have reported that in pregnancies with GDM that also develop PE, impedance to flow in the UtAs was increased compared with pregnancies in which PE did not develop.…”
Section: Introductionmentioning
confidence: 99%